PENINGKATAN PEREKONOMIAN DESA MELALUI PROMOSI PENJUALAN KERUPUK SANGRAI DI DUSUN BANGLAYAR DESA TENTENAN BARAT KECAMATAN LARANGAN KABUPATEN PAMEKASAN - Khairul Umam; Encung Encung (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2022)
Mentoring can be understood as a community empowerment activity by placing escorts as facilitators, communicators, motivators and dynamators. Basically, mentoring is an effort to include the community in developing various potentials so as to achieve a better quality of life. In addition, it is directed to facilitate decision-making processes related to the needs of the community, build the ability to increase revenue, carry out business-scale business and develop planning and implementation of participatory activities. Society grows and develops as a whole family. The head of the family and his family members are the drivers and triggers of business progress. This principle requires chaperones to empower all family members to participate in increasing income and welfare. Groups in society grow and develop on the basis of their willingness and ability to learn for themselves what they need and what they will develop, including efforts to change their livelihoods and lives. Groups grow out of, by and for the benefit of society. In addition to its own group members, cooperation is also developed between the group and other partners so that their business develops, increases income and welfare and is able to form economic institutions. Roast food is one of the assets in the village of West Tentenan Pamekasan. Where this food is different from the rest of the krupuk. By cooking through the sand so that it tastes different from the usual food.